Doctoral Programs in Accounting . - Anthony, Robert N.; Dunn, Clarence L.; Nelson, Cari L.; Salmonson, Roland F.; Wheeler, John; Stone, Williard E. (The Accounting Review, 1965)
Abstract The article presents information on recommendations made by the 1964 American Accounting Association Committee on Doctoral Programs. The committee was charged to investigate and to make appropriate recommendations concerning doctoral programs with a concentration in accounting. The primary role of doctoral programs in accounting at the present time is to prepare the student for university teaching of accounting. There are indications that the future may place increasing demands upon such doctoral programs to prepare students for a research career in public or industrial accounting. The increasing number applying for entrance to doctoral programs each year makes it possible for universities to exercise greater selectivity in the choice of students. The courses in accounting should cover thoroughly the areas of financial accounting, management accounting and the analytical uses of accounting data. Doctoral courses should be based upon an educational philosophy distinct from those of undergraduate and advanced professional programs offered by a university.